2021
DOI: 10.35551/pfq_2021_3_6
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding in Kenya: Factors for Successful Campaign : The Case of Kickstarter Crowdfunding Platform

Abstract: The study aimed at investigating the factors that lead to successful crowdfunding campaigns in Kenya. The success factors of reward-based crowdfunded campaigns vary in different countries due to differences in cultures, legal requirements, social interactions, political and business environments. With very minimal research on crowdfunding funding in Kenya, the study therefore, aimed at analyzing reward-based crowdfunding in Kenya using Kickstarter data, and identifying the crucial factors necessary to run a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…In addition to that, the higher number of backers contributing to the crowdfunding platform increases the probability of success rate as compared to the lower number of backers. Hence, the results are in line with the findings by Mollick (2014) and Wachira (2021).…”
Section: Crowdfunding In Africa: Which Models Are the Most Popularsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to that, the higher number of backers contributing to the crowdfunding platform increases the probability of success rate as compared to the lower number of backers. Hence, the results are in line with the findings by Mollick (2014) and Wachira (2021).…”
Section: Crowdfunding In Africa: Which Models Are the Most Popularsupporting
confidence: 92%
“…However, in Africa, crowdfunding is still at the infancy level due to limited technological infrastructure and internet usage (Chao et al 2020). Regardless of the low adoption of crowdfunding in Africa, crowdfunding has potential to provide access to finance to entrepreneurs (Wachira 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there was little literature on crowdfunding focusing on Africa during the COVID-19 pandemic. Hence, this study fills the research gaps identified by scholars such as Wachira [11], Zribi [7], and Igra et al [19]. Further, although there are studies that examined the effects of the COVID-19 pandemic on crowdfunding performances [7,8,[19][20][21], these studies were confined to developed countries; hence, their findings do not necessarily yield similar results for Africa.…”
Section: Introductionmentioning
confidence: 77%
“…Hence, from the vantage point of the transformational entrepreneur social theory, crowdfunding has the potential to overcome problems created by the COVID-19 pandemic in relation to access to finance. A crowdfunding platform alleviates the limited access to financing due to its popularity and growth, especially in Africa [11].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation